Comparison of seismic design provisions for buckling restrained braced frames in Canada, United States, Chile, and New Zealand. (November 2016) - Tremblay, R.; Dehghani, M.; Fahnestock, L.; Herrera, R.; Canales, M.; Clifton, C.; Hamid, Z.
Abstract: Seismic design provisions for buildings in Canada, the United States, Chile and New Zealand are presented for buckling restrained braced frames, with focus on design requirements for seismic stability. P-delta effects are explicitly considered in seismic design in Canada, the U.S. and New Zealand. In Chile, stability effects are limited by means of more stringent drift limits. The provisions are applied to a 9-storey building structure located in areas in each country having similar seismic conditions. For this structure, comparable seismic loads are specified in Canada and Chile, whereas significantly lower seismic effects are prescribed in the U.S. In all countries, use of the dynamic (response spectrum) analysis method resulted in lighter and more flexible structures compared to the equivalent static force procedure. Seismic stability requirements had greater impact on designs in Canada and New Zealand. Frame design in the U.S. was only affected by stability effects when applying the stability requirements from AISC 360-10.